Hermenêutica do cuidado pastoral: a paradoxalidade da hermenêutica contemporânea - Rocha, Abdruschin Schaeffer (2010)
This thesis has as its presupposition the understanding that the present time named the contemporary displays a paradoxical character, which is justified through the simultaneity of illuminist and post-modern worldviews. Such paradoxical character demands a paradoxical hermeneutics that may become the foundation to the construction of a hermeneutics of care, with a special focus on pastoral care. The work starts by noting certain confusion in the notions of modernity and post-modernity, in order to present the concept of the contemporary. The contemporary collapses the illuminist and the post-modern worldviews and creates the possibility to investigate three relationships in contemporary hermeneutics: the first one is the relationship between closed-disclosed under the sign of re-velation. This concept of revelation stands in contrast to the illuminist one identical to the Hegelian Offenbarung. Karl Barth and Heidegger open the way at this juncture. The second relationship investigates the possibilities of a hermeneutics built on the dialectic between tradition and emergence, memory and the forgotten. The third relationship has its focus on a hermeneutics under the dialectic between action and affection. It will show the dangers of an epistemology solely based on action prone to a strong metaphysical thought and the need of an epistemology also based on being affected. In this way it will accomplish the task of launching the foundations for a new contemporary hermeneutics. The second part of the thesis starts from this contemporary hermeneutics that sees all reality, texts and people, as the object of interpretation. Therefore, it tries to understand the nuances that define the texts in motion (people), in order to propose a hermeneutics of pastoral care. Its starting point is the Heideggerian concept of care as a mode of being human. The second step is a discussion of, based on 2 Corinthians 3:1-3, the hermeneutics of the living letters, metaphor that is taken as a hermeneutical model. The metaphor of the living letters emphasizes the being-ness of human beings and settles the basis for such a hermeneutics. The notions of world, other and Other as constitutive of human being also serve as a foundation to the being-ness of the pastoral care. Finally, the thesis proposes three hermeneutical dimensions of pastoral care, built on the paradoxical relationships displayed by the dialectics between action-affection; tradition-emergence; closed-disclosed.